2015
DOI: 10.1111/jfpp.12594
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physical, Thermal, Pasting Characteristics and Mineral Profile of Pigmented and Nonpigmented Rice Cultivars

Abstract: Physical, thermal and pasting properties of pigmented and nonpigmented rice cultivars were investigated in the present study. The mineral profiles for 11 minerals were also investigated. Physical characterization of the rice cultivars was analyzed by measurement of axial dimension, angle of repose, etc. In pasting properties, RR 2 (Umling ame red rice) showed higher pasting temperature (90.5C), final viscosity (3,477 cP) and set back viscosity (1,876 cP) than RR1 (Lingkang taker ame red rice) and WR (Pungpo ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Chávez‐Murillo et al (2011) mentioned that in general, different rice varieties of India have T o in the range of 61.1–75.76°C, T p in the range of 66.91–79.21°C and T c in the range of 71.93–84.59°C, respectively. But the values obtained in the present study on pigmented rice (Table 4) are higher than the above indicated range and was in line with Samyor et al (2015) for pigmented rice. The presence of fat (1.52 ± 0.02 g/100 g in raw rice) may marginally increase melting temperature.…”
Section: Resultssupporting
confidence: 92%
“…Chávez‐Murillo et al (2011) mentioned that in general, different rice varieties of India have T o in the range of 61.1–75.76°C, T p in the range of 66.91–79.21°C and T c in the range of 71.93–84.59°C, respectively. But the values obtained in the present study on pigmented rice (Table 4) are higher than the above indicated range and was in line with Samyor et al (2015) for pigmented rice. The presence of fat (1.52 ± 0.02 g/100 g in raw rice) may marginally increase melting temperature.…”
Section: Resultssupporting
confidence: 92%
“…Two pigmented rice cultivars (red rice: RR 1, and red rice: RR 2 ) and white (WR) from Manigong, Arunachal Pradesh, India showed the presence of various important micronutrients viz.,Al (0.97 mg/100 g), (Cr 0.19 mg/100 g), Mg (54.25 mg/100 g), K(29.00 mg/100 g), Zn (0.65 mg/100 g), Na(19.54 mg/100 g) and Ca (9.55 ± 0.18 mg/100 g) and were observed highest in RR 1 than RR 2 and WR (Samyor et al ., 2016b). Recently, a study reported that two black rice varieties from Korea viz.,Heukjinjubyeo, and Heukgwangbyeo evinced higher amount of Ca and K when compared with a white variety (Heuknambyeo) (Hiemori et al .,).…”
Section: Various Bioactive Compounds Present In Pigmented Ricementioning
confidence: 99%